2023
DOI: 10.18632/aging.204517
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of BUBs gene family in lung adenocarcinoma with immunological analysis

Abstract: Lung adenocarcinoma (LUAD) is one of the most commonly malignant tumors, and major challenges remain in the treatment of LUAD. Budding uninhibited by benzimidazole 1/3 (BUB1/3) play significant roles in the process of spindle-assembly checkpoint (SAC) during mitosis. However, their roles in LUAD have not been established. Here, we performed an immunological analysis of BUB1/3 in LUAD using a comprehensive bioinformatics approach, quantitative real-time-PCR and Western blotting technique. Our results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
3
0
0
Order By: Relevance
“…further emphasizes its significance in lung cancer. No correlation between BUB1 expression and cancer stage or grade was observed (Figures 1J-K), consistent with findings in other cancers including LUAD (12,24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…further emphasizes its significance in lung cancer. No correlation between BUB1 expression and cancer stage or grade was observed (Figures 1J-K), consistent with findings in other cancers including LUAD (12,24).…”
Section: Discussionsupporting
confidence: 89%
“…Confirmation of BUB1 overexpression in tumor tissues ( Figures 1H-I and 1L ) and lung cancer cell lines ( Figure 1M ) further emphasizes its significance in lung cancer. No correlation between BUB1 expression and cancer stage or grade was observed ( Figures 1J-K ), consistent with findings in other cancers including LUAD (12, 24).…”
Section: Discussionsupporting
confidence: 89%
“…Significantly increased UBE2C expression level in various tumor types, including CESC, CHOL, GBM, and UCS tumors (with AUC = 100%) or in ACC, BLCA, BRCA, COAD, ESCA, KICH, KIRC, KIRP, LGG, LIHC, LUAD, LUSC, OV, PAAD, READ, SKCM, STAD, TGCT, and UCEC tumors (with AUC ≥90%) suggest that assessing UBE2C gene expression could serve as a novel biomarker for tumor staging and a promising diagnostic tool prior to symptoms manifestation. The diagnostic value of UBE2C has been previously reported in patients with hepatocellular carcinoma (HCC) and liver cancer 42,43 . Consistently, a recent study reported that detecting of UBE2C expression level through IHC sections could be an indicator of polyploidy in cancer tissue, allowing discrimination of aggressive subsets of HCC.…”
Section: Discussionsupporting
confidence: 62%